2021
DOI: 10.1016/j.celrep.2021.108843
|View full text |Cite
|
Sign up to set email alerts
|

The AD tau core spontaneously self-assembles and recruits full-length tau to filaments

Abstract: Highlights d The AD tau filament core spontaneously aggregates in the absence of an inducer d Aggregation and seeding of full-length wild-type tau are enhanced by the AD tau core d The AD tau core templates abnormal tau in brain and antemortem CSF from AD patients d Tau filament cores from the tauopathies CBD and PiD also spontaneously aggregate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 55 publications
(86 reference statements)
1
20
0
Order By: Relevance
“…To obtain a sufficient yield of tau filaments from PSP tissue, we evaluated the amount of tau present within the sarkosyl-insoluble (P3) fraction from four different brain regions in three different PSP cases, without pronase-treatment to preserve posttranslational modifications (Arakhamia et al, 2020;Carlomagno et al, 2021). As tau levels were consistently highest in the P3 fractions from caudate and frontal cortex, we screened these two regions in an additional 12 PSP cases.…”
Section: Psp Casementioning
confidence: 99%
“…To obtain a sufficient yield of tau filaments from PSP tissue, we evaluated the amount of tau present within the sarkosyl-insoluble (P3) fraction from four different brain regions in three different PSP cases, without pronase-treatment to preserve posttranslational modifications (Arakhamia et al, 2020;Carlomagno et al, 2021). As tau levels were consistently highest in the P3 fractions from caudate and frontal cortex, we screened these two regions in an additional 12 PSP cases.…”
Section: Psp Casementioning
confidence: 99%
“…The same was true of K11 and K12 constructs (tau residues 244–394 for K11, and the same sequences, excluding R2, for K12) ( Wille et al, 1992 ). Moreover, proteins comprising the ordered cores of tau filaments from AD [residues 306–378], PiD [residues 254–378, but excluding R2], and CBD [residues 274–380] have been reported to assemble into filaments ( Carlomagno et al, 2021 ). It remains to be established if the structures of these filaments resembled those from diseased brain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being involved in the assembly of the cytoskeleton, Tau can also bind to other proteins and play a role in cell signaling through phosphorylation. When the phosphorylated regulatory system of Tau is disrupted, such as by hyperphosphorylation, neurological symptoms such as cognitive decline can emerge ( Gratuze et al, 2018 ; Li et al, 2019 ; Carlomagno et al, 2021 ). Numerous studies have shown that neuronal tangle formed by hyperphosphorylated polymerization of Tau protein is another hallmark pathological feature of AD in addition to Aβ deposition ( Hanger et al, 2007 ; Reynolds et al, 2008 ).…”
Section: Phosphatidylinositol-specific Phospholipase C Gamma 2 Acts A...mentioning
confidence: 99%